# Answer on Trigonometry Question for aidan

Question #2670

Prove that:&

cos (θ-φ ) - sin (θ+φ/2) =-2 cos θ

cos (θ-φ ) - sin (θ+φ/2) =-2 cos θ

Expert's answer

This formula is not correct:

If θ=φ=0, then

The left-hand side is equal to

& cos 0 – sin 0 = 1,

while the right-hand side is

-2cos0 = -2

If θ=φ=0, then

The left-hand side is equal to

& cos 0 – sin 0 = 1,

while the right-hand side is

-2cos0 = -2

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment